School Based Management Model for Improving Education Quality at SMA Linggang Bigung - Afriyanti, Afriyanti; Gede, Widyatmike; Dwiyono, Yudo (Jurnal Educatio FKIP UNMA, 2025)
This research aims to describe the planning, organization, implementation, and supervision of the school-based management model at SMA Negeri Linggang Bigung. This type of research is qualitative case study. Data were collected through interviews and observations at two high schools in Linggang Bigung. The informants in this study included the Principal, Curriculum Vice Principal, Student Affairs Vice Principal, teachers, and students. Data were analyzed by organizing, deconstructing, reconstructing, interpreting, and concluding. Triangulation techniques were used to test the validity of the data, specifically technique and source triangulation. The school-based management model implemented at SMA Negeri Linggang Bigung is School-Based Quality Improvement Management (MPMBS).The results indicate that MPMBS planning is carried out by analyzing needs, formulating vision, mission, and targets/objectives, analyzing infrastructure, and involving parents and the community. In terms of organization, SMA Negeri Linggang Bigung exhibits autonomy, partnerships, active community participation, openness, and accountability. Regarding implementation, SMA Negeri Linggang Bigung has a safe and orderly school environment, quality mission and targets, strong leadership, expectations, staff development, repeated evaluations, as well as intensive communication and support from parents and the community. The supervision conducted at SMA Negeri Linggang Bigung is in accordance with content standards, process standards, competency standards, educator and educational staff standards, infrastructure standards, management standards, financing standards, and assessment standards. Thus, it can be concluded that the implementation of the MPMBS model at SMA Negeri Linggang Bigung involves careful planning, inclusive organization, structured execution, and standard-based supervision. This has implications for academic performance, student character development, and school management effectiveness, which in turn affects parental satisfaction and students' future prospects.